Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2021)
A dataset containing 39186037 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is one of (Anas platyrhynchos Linnaeus, 1758, Anas poecilorhyncha J.R.Forster, 1781, Anas puna Tschudi, 1844, Anas rhynchotis Latham, 1801, Anas rubripes Brewster, 1902, Anas sibilatrix Poeppig, 1829, Anas strepera Linnaeus, 1758, Anas superciliosa J.F.Gmelin, 1789, Anas undulata C.F.Dubois, 1838, Anas versicolor Vieillot, 1816, Anser albifrons (Scopoli, 1769), Anser anser (Linnaeus, 1758), Anser brachyrhynchus Baillon, 1834, Anser cygnoides (Linnaeus, 1758), Anser erythropus (Linnaeus, 1758), Anser fabalis (Latham, 1787), Anser indicus (Latham, 1790), Anseranas semipalmata (Latham, 1798), Aythya americana (Eyton, 1838), Aythya baeri (Radde, 1863), Aythya collaris (Donovan, 1809), Aythya ferina (Linnaeus, 1758), Aythya fuligula (Linnaeus, 1758), Aythya novaeseelandiae (J.F.Gmelin, 1789), Aythya nyroca (Güldenstädt, 1770), Aythya valisineria (A.Wilson, 1814), Branta bernicla (Linnaeus, 1758), Branta canadensis (Linnaeus, 1758), Branta canadensis (Linnaeus, 1758))", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 39186037 records from 1590 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0204792-200613084148143/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences